Factors Affecting Mother's Behavior on The Compliance of Antenatal Care Visits - Sirli Mardianna Trishinta; Pertiwi Perwiraningtyas; Susmini Susmini (Journal of Ners and Midwifery, 2022)
Antenatal care is very important in ensuring that both the mother and the fetus will survive during pregnancy and during delivery. ANC service is a planned program in the form of observation, education, and medical treatment for pregnant women. The purpose of the research was to determine the factors that influence the mother's behavior on the compliance of Antenatal Care Visits at the Anggrek and Mawar Posyandu, Tlogomas Village, Malang City. The research design used analytic observation. The population of this research was all pregnant women in Posyandu Anggrek and Mawar, Tlogomas Village, Malang City as many as 17 people. The sample was 17 respondents taken by total sampling technique. The data collection technique used an instrument in the form of a questionnaire. The data analysis method used the Chi Square test (p value <0.05). The results showed that most of the respondents (64.7%) had sufficient knowledge, most of the respondents (70.6%) had the attitude of the sufficient category, and most of the respondents (52.9%) had the husband's support in the sufficient category and most of the respondents (64.7%) had the level of compliance of visits in the right category. The results of the chi square test showed that there was a correlation between knowledge, attitudes and husband's support factors on the compliance of Antenatal Care Visits at the Anggrek and Mawar Posyandu, Tlogomas Village, Malang City. Further researchers are expected to conduct similar research by exploring other factors that can affect the compliance of ANC visits such as economic factors, distance from health facilities and this research is carried out by visiting respondents one by one so that it is less effective.